Efektifitas Edukasi E-Komik Terhadap Tingkat Pengetahuan Tentang Pertolongan Pertama Korban Laka Lantas: Efektifitas Edukasi E-Komik Terhadap Tingkat Pengetahuan Tentang Pertolongan Pertama Korban Laka Lantas - Zhafiirah; Dendy Kharisna; Wardah; Ulfa Hasanah (Jurnal Keperawatan Terapan, 2026)
The number of traffic accidents in Indonesia is still very high, where every year almost 1.3 million people die due to these accidents, and millions of others are injured. Of these accident victims, approximately 30% are children and adolescents, who are the nation's future generation. More than 30% of traffic accident victims are under 25 years old. Traffic accidents are the most dangerous cause of death for people aged 15-29 years. This study aims to determine the effect of E-Comic-based education on the level of knowledge of students at SMAN 1 Pekanbaru City. This type of research is quantitative using a design (Quasy Experiment) with a Pre-test Post-test Nonequivalent Control Group Design approach. This study was conducted at SMAN 1 Pekanbaru City with a total of 40 respondents who were conducted for 1 day. The results of this study obtained a difference in the average knowledge score in the intervention group of 21.65 and a difference in the control group of 12.45. Although both experienced an increase, the average knowledge score in the intervention group was higher than the control group, which means that e-comic-based education is more effective in increasing knowledge than education that only provides PowerPoint. The results of the t-dependent statistical test showed a p-value of 0.000 for the intervention group and the control group, which means a p-value <0.05, so the hypothesis H0 is rejected, which means that e-comics are effective in increasing knowledge about first aid for traffic accident victims at SMAN 1 Pekanbaru City. The results of the t-independent sample t-test showed a p value of 0.003 which means Sig. (2-tailed) <0.05, so the hypothesis H0 was rejected, which means there was a significant difference between the intervention group and the control group. Based on the results of the study, it can be concluded that e-comic-based education is effective in increasing students' knowledge about first aid for traffic accident victims. Keywords: Traffic accidents, Knowledge, e-Comics